Influence of adolescents in family food decision making in Klang Valley, Malaysia - Wan Ismail, Wan Rusni (2012)
The importance of understanding target market is crucial for the survival of business. Marketers and retailers put a lot of effort to understand how family arrived at their purchase decision because decisions in a family are not solely made by parents. Certain decisions, especially food-related decision are highly influenced by children and surprisingly parents sometime do not even realize it. This notion is supported by previous studies which suggest that level of influence children have in family decision is product related, for instance children exert high influence in low involvement product, which is less expensive such as food. Interestingly, teenagers’involvement was also found in high involvement product such as mobile phone. With very little evidence available on children’s influence in Malaysia it is very difficult to determine the level of influence that Malaysian children have in their family decision making. In addition, there is no available data to ascertain teenagers’ specific characteristic such as age group or demographic background that proves to be more influential in family decision making. This study attempted to investigate teenagers influence on family food decision making based on their utilization of bilateral strategies. One of the unique characteristic of bilateral strategies is the need for both parents and teenagers cooperation to make it work. For instance, teenagers assist parents with consumer and tasks around the house hoping that parents will comply to their request for certain specific items they need or want. A total of 500 questionnaires were distributed to teenager’s age between 13 to 17 years old in selected secondary schools in Klang Valley using simple random sampling technique. Data were then \analyzed using the SPSS version 20 software. Descriptive analysis gives a general description of the respondents while comparative analysis t-Test and One way ANOVA were performed to test the differences between relevant data. Apart from that, Pearson Correlation is used to establish relationship between teenagers’ demographic and their involvement in family food decision making. Multiple regression analysis is also performed to identify the best model for this study. Bilateral strategies tested in this study have yield positive and strong correlation between all consumer activities tested namely suggesting price, product and store with perception of reward. This result will provide important data for marketers and retailers because teenagers were reported to be highly involved with such activities while older teenagers reported less involvement in consumer activities. On the other hand, performing task does not resulted with increase in influence in family food decision making, thus suggest that involvement in such activities is highly particularistic, thus the reward in form of love is more important than material goods. Apart from that, this study also found coalition strategy to influence parents purchase. Initially it is thought that single child in the family is more influential. However teenagers with three or more siblings reported high influence in family decision which indicate coalition pattern in influence attempt. Besides that, this study also highlighted the differences in influence among the three races which are Malay, Chinese and Indian which is an indication that Malaysian has difference purchasing behaviour. The finding from this study will help marketers to identify the specific family members to target rather than just targeting family, this to ensure that promotional message will be delivered to specific target effectively. Besides that, the differences in purchasing behaviour among various races should also indicate the need for developing specific promotional strategy for difference races. Future researches should focus on the different type of consumer activities because this study shows that teenagers’ involvement in consumer activities such as suggesting price, product and store are part of their strategies to influence their parents’ final decision. Apart from that, future research should also look into actual income when investigating differences in family influence rather than dual income, as dual income does not lead to positive findings in this study. Finally future studies adolescents’ involvement in such activities is a good indication that these teenagers are around when the purchase is made. Interestingly younger also test teenagers’ influence from other parts of Malaysia, including the rural areas in order to generalize the findings to the whole nation.